Indigenous Marriage and Family Counseling among Oromo Community in Ethiopia - Getachew Abeshu Disassa; Tsehay Baissa Into (Universidade Estadual de Alagoas, 2020)
Semi-structured interview and FGD was employed to extract information from thirteen respondents selected purposefully. The result of the study disclosed that marriage and family counseling is a tradition among Oromo community right after shaving of born hair. Mostly, the father takes responsibility of the male and mother follows her daughter. 'Kuchu' and engagement counseling, and knowledge of blessing and curse are among the major areas of concern. Consequently, principles of marriage and family counseling, procedures and ages of application are fundamental. Incorporating indigenous knowledge and skills of counseling in education curriculum and training for its sustainability was recommended for upgrading.